How Social Network Site Users' Motives Predict Their Online Network Sizes: A Quantile Regression Approach to Japanese Twitter Usage. Issue 7 (21st April 2019) - Kitamura, Satoshi; Kawai, Daisuke; Sasaki, Yuichi
ABSTRACT: This study examines the relationships between Twitter users' motives for using the service and their egocentric network sizes on Twitter in terms of online social capital. Based on the literature, we focus on quantiles of egocentric network sizes rather than on means. The respondents were 1, 559 Japanese Twitter users; they participated in an online survey and allowed us to collect their log data on Twitter. A socializing motive was associated with the number of mutual follows only in the lower tails of the size distribution and was negatively linked to the number of one-sided follows. In contrast, an information-seeking motive was positively related to the number of one-sided follows. These findings suggest that cognitive constraints exert an effect on socializing through an online service.